Structural testing of a shear web attachment point on a composite lattice cylinder for aerospace applications. (1st May 2021) - Smeets, Bart J.R.; Fagan, Edward M.; Matthews, Kelly; Telford, Robert; Murray, Brendan R.; Pavlov, Leonid; Weafer, Bryan; Meier, Patrick; Goggins, Jamie
Abstract : Lattice structures offer enhanced stiffness-to-weight characteristics for structures in highly mass sensitive applications like aviation and aerospace. The adaptability of composite materials allows for further optimisation of the structural layout of the lattice to reduce mass for primary aerospace structures. The attachment point on the lattice is a key structural feature, defining the interaction between the payload and the primary structure. The present work investigates an attachment point design for a lattice satellite central cylinder approximately 1.5 m in diameter, manufactured using composite prepreg fibre placement. This work presents the design, experimental testing and numerical analysis of attachment points consisting of filled patches in the lattice. The points were loaded in shear and the responses of the surrounding helical and hoop ribs of the lattice were monitored using strain gauges, LVDTs and a digital image correlation system. The measured response of the structure validated numerical predictions and the numerical design methodology.